Children of substance abusers: psychosocial profile of children and adolescents / Os filhos de usuários nocivos de substâncias psicoativas: Perfil psicossocial das crianças e dos adolescentes - de Grandi, Camila Garcia; Vilela, Thaís dos Reis; Figlie, Neliana Buzi (Cadernos Brasileiros de Terapia Ocupacional, 2014)
Introduction: Psychoactive substance abuse problems in the family have an impact on the development of children and adolescents. This risk conditions can harm mental health and hinder healthy development in psychosocial areas. Objectives: This study investigated the psychosocial profile of children and adolescents assisted in a prevention service center for children of substance abusers in a deprived community located in the outskirts of Sao Paulo. Methods: Exploratory and descriptive study, based on cross-sectional methodology and a convenience sample of 791 children and adolescents assisted at the Intervention and Support Center for Children of Substance Abusers - CUIDA between January 2001 and December 2008. The sample was divided into groups according to discharge status: Active, Therapeutic Discharge (TD), Abandonment, Without Information about the Reason for Leaving and With Information about the Length of Treatment (WIRL), Without Information (WI), and Other Reasons for Leaving (OR). Results: In the Active group, 26% of mothers had completed high-school and 11% belonged to the A/B socioeconomic classes. The TD group showed the highest percentages of wage earning parents (52%) living together (64%). In the WIRL group, 17% of the mothers were illiterate or had not completed primary education, and 23% of the fathers were unemployed. In the WI group, 22% lived in houses that had been lent to them. Conclusions: Results indicate the impact of addiction and underprivileged conditions (such as housing status, fathers’ level of education, and socioeconomic status) on retention in the service and the importance of health prevention and promotion strategies aimed at this population.